Metabolic and Bariatric Surgery Patients' Preoperative Dieting Attempts and Associations With Postoperative Outcomes - LeeAnn C. Swager; Keeley J. Pratt; Haley M. Kiser; Ashleigh A. Pona (Obesity Science & Practice)
ABSTRACT Purpose Pre‐operative eating disorders are well documented within the metabolic and bariatric surgery (MBS) population, yet subthreshold dieting attempts are less understood. The objectives of this study were to define and categorize patients' preoperative dieting attempts, and to determine how attempts are associated with postoperative outcomes, eating disorders, and demographics. Materials and Methods Three hundred twenty‐one patients (81.0% female; 68.3% White) who had MBS (57.3% Roux‐en‐Y) between 2019 and 2020 were included. Preoperative dieting attempt responses were categorized as provider‐managed, non‐medically managed, and self‐directed attempts; subtypes of dieting methods (e.g., low calorie) were described. Descriptive analyses were conducted for attempt categories and subtypes, and between attempts and readmissions, complications, eating disorders, and demographics. ANOVAs determined associations between attempts and %TWL at 6 and 12 months. Results Patients reported an average of five to six preoperative dieting attempts; self‐directed attempts were the most common (91.9%), and exercise was the most common subcategory (70.7%). Patients with  ≥ 1 provider‐managed attempt were less likely to experience a complication (p < 0.001) and more likely to experience readmission (p = 0.018). Patients with 1 self‐directed attempt were less likely to experience a complication (p = 0.045) and readmission (p < 0.001). Patients who experienced  ≥ 2 low fat diet attempts were more likely to have complications (p < 0.001) and readmissions (p = 0.008); patients with  ≥ 2 VLCD attempts were more likely to have a complication (p < 0.001). Patients who experienced  ≥ 2 non‐medically managed attempts had higher preoperative BMIs (p = 0.03). Discussion Given that patients engaged in frequent dieting attempts that fall outside formal assessments, future work should seek to expand pre‐operative assessments.